The Christian Labour Association of Canada (CLAC): Between Company and Populist Unionism - Tufts, Steven; Thomas, Mark (Labour / Le Travail, 2017)
The Christian Labour Association of Canada (clac) has historically had a relatively small presence in Canada's labour movement. Increasing interest in clac over the last decade is due to its expanded membership, largely in western Canada and Ontario: the union claims to represent 60,000 workers. Further, the tactics used to achieve this growth have been controversial within organized labour. In fact, clac was expelled from central labour bodies for its employer accommodationist strategies. This article expands the understanding of clac beyond a characterization of classic "company" unionism. In this article we find that clac integrates elements of populism into a specific geographic strategy for expansion in ways that complicate analysis. We focus on labour board records of disputes between clac and other unions, a recent case where the union backed employer-friendly legislation in Ontario, and the union's rhetorical devices and propaganda.